PENGARUH KEGIATAN FORDIKA DALAM MENGUATKAN KARAKTER INTEGRITAS MAHASISWA PPKN FKIP UNILA - Nadya Paramitha; Yunisca Nurmalisa; Nurhayati Nurhayati; Ana Mentari; Abdul Halim (STKIP Subang, 2026)
This study aims to determine the effect of Forum Pendidikan Kewarganegaraan (FORDIKA) activities on strengthening the integrity character of students of the Civic Education Study Program, Faculty of Teacher Training and Education, University of Lampung. This research employed a quantitative descriptive approach. The subjects were 74 students selected using random sampling techniques. Data were collected through questionnaires as the primary instrument, supported by interviews and documentation. The integrity character was measured using indicators of honesty, courage, wisdom, and responsibility. The instrument had been tested for validity and reliability before being distributed. Data were analyzed using simple linear regression with SPSS. The results showed that FORDIKA activities significantly influenced students' integrity character, with a significance value of 0.000 (<0.05). The coefficient of determination (R Square) was 0.281, indicating that FORDIKA activities contributed 28.1% to strengthening students' integrity character. Activities such as Bela Negara, Civic Family, and the Civic Education Olympiad provide opportunities for students to develop honesty, responsibility, courage, and wisdom through organizational participation. Therefore, FORDIKA activities play an important role in strengthening students' integrity character.